p-49=5(p+3)

Simple and best practice solution for p-49=5(p+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for p-49=5(p+3) equation:


Simplifying
p + -49 = 5(p + 3)

Reorder the terms:
-49 + p = 5(p + 3)

Reorder the terms:
-49 + p = 5(3 + p)
-49 + p = (3 * 5 + p * 5)
-49 + p = (15 + 5p)

Solving
-49 + p = 15 + 5p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-5p' to each side of the equation.
-49 + p + -5p = 15 + 5p + -5p

Combine like terms: p + -5p = -4p
-49 + -4p = 15 + 5p + -5p

Combine like terms: 5p + -5p = 0
-49 + -4p = 15 + 0
-49 + -4p = 15

Add '49' to each side of the equation.
-49 + 49 + -4p = 15 + 49

Combine like terms: -49 + 49 = 0
0 + -4p = 15 + 49
-4p = 15 + 49

Combine like terms: 15 + 49 = 64
-4p = 64

Divide each side by '-4'.
p = -16

Simplifying
p = -16

See similar equations:

| -30-5n=-6(n+4) | | -135/-9=15 | | 10(s-6)=-149 | | 8x+11+3=23-7x+4 | | 5(v-3)=-9v-29 | | 44c+49=457c-7 | | 8(X-1)=-2x+52 | | 9(x+1.4)=18 | | -3(6x-8)+7=-18+31 | | 2(x+7)+6=2x+2 | | 7x=5(2x-5) | | 12(r-5)=60 | | -4-4p=24 | | 3x+1-1=3x+2 | | 20x(4-2)= | | 4(7v-8)=136 | | 8X+12Y=(X+Y) | | 2(y-5)=7y+8 | | 3y-2x=m | | N^2-81n=0 | | -9p-4=50 | | -8(n-1)=5-8n | | -9p-4=40 | | =9E-07(551.368) | | 49=413c-7 | | 10(3x-5)=100x | | -5(4y-2)-y=-4(y-2) | | 6n+3n+3120=5400 | | -6+-1y=10 | | -7p-4=2p+40 | | 17=102 | | 6+-1y=10 |

Equations solver categories